KEA-1010, a ketamine ester analogue, retains analgesic and sedative potency but is devoid of Psychomimetic effects - Martyn Harvey; Jamie Sleigh; Logan Voss; Mike Bickerdike; Ivaylo Dimitrov; William Denny (BMC, 2019)
Abstract Background Ketamine, a widely used anaesthetic and analgesic agent, is known to improve the analgesic efficacy of opioids and to attenuate central sensitisation and opioid-induced hyperalgesia. Clinical use is, however, curtailed by unwanted psychomimetic effects thought to be mediated by N-methyl-D-aspartate (NMDA) receptor antagonism. KEA-1010, a ketamine ester-analogue designed for rapid offset of hypnosis through hydrolysis mediated break-down, has been shown to result in short duration sedation yet prolonged attenuation of nociceptive responses in animal models. Here we report on behavioural effects following KEA-1010 administration to rodents. Methods KEA-1010 was compared with racemic ketamine in its ability to produce loss of righting reflex following intravenous injection in rats. Analgesic activity was assessed in thermal tail flick latency (TFL) and paw incision models when injected acutely and when co-administered with fentanyl. Tail flick analgesic assessment was further undertaken in morphine tolerant rats. Behavioural aberration was assessed following intravenous injection in rats undergoing TFL assessment and in auditory pre-pulse inhibition models. Results KEA-1010 demonstrated an ED50 similar to ketamine for loss of righting reflex following bolus intravenous injection (KEA-1010 11.4 mg/kg [95% CI 10.6 to 12.3]; ketamine (racemic) 9.6 mg/kg [95% CI 8.5-10.9]). Duration of hypnosis was four-fold shorter in KEA-1010 treated animals. KEA-1010 prolonged thermal tail flick responses comparably with ketamine when administered de novo, and augmented morphine-induced prolongation of tail flick when administered acutely. The analgesic effect of KEA-1010 on thermal tail flick was preserved in opioid tolerant rats. KEA-1010 resulted in increased paw-withdrawal thresholds in a rat paw incision model, similar in magnitude yet more persistent than that seen with fentanyl injection, and additive when co-administered with fentanyl. In contrast to ketamine, behavioural aberration following KEA-1010 injection was largely absent and no pre-pulse inhibition to acoustic startle was observed following KEA-1010 administration in rats. Conclusions KEA-1010 provides antinociceptive efficacy in acute thermal and mechanical pain models that augments standard opioid analgesia and is preserved in opioid tolerant rodents. The NMDA channel affinity and psychomimetic signature of the parent compound ketamine is largely absent for KEA-1010.